Derecho constitucional y reeleccion presidencial. Sentencia del Tribunal Constitucional No. 2771 del 2003 - Romero-Pérez, Jorge Enrique (2015)
This essay commemorates 12 years of the promulgation of Ruling No. 2717 of 2003 of the Constitutional Court. In these twelve years, there have been outcomes of this majority vote. The most important of those effects is that that it allowed politician and businessman Oscar Arias Sánchez to become President of Costa Rica for a second time, from 2006 to 2010, on account of this second judgment (2003) that was favorable to him with a vote of 5 to 2, compared to the previous vote of 2000, that was unfavorable for him with a vote 4 to 3.